Association of hand grip strength with rheumatoid arthritis and osteoarthritis in the Korean population: A large-scale cross-sectional study - Jeong Hee Chi; Bum Ju Lee (PLoS ONE, 2026)
Background Low hand grip strength (HGS) is associated with osteoarthritis (OA) and rheumatoid arthritis (RA), but no studies have simultaneously examined the associations of OA/RA with HGS indices. The objective was to examine the associations between absolute/relative HGS and the risk of OA, RA, and combined OA and RA (OR-arthritis). Methods This large-scale cross-sectional study was based on data from the Korea National Health and Nutrition Examination Survey. A complex survey sample design was applied to the entire Korean population. Associations of OA, RA, and OR-arthritis with HGS and anthropometric indices were examined by binary logistic regression in unadjusted and adjusted analyses. Results The prevalence of OA and RA was 8.2% and 1.1%, respectively, in men and 26.9% and 2.2%, respectively, in women. The prevalence of OR-arthritis was 1.4% in women. In men, OA was strongly associated with the waist-to-height ratio (WHtR) and HGS in both hands divided by the WHtR. RA had the strongest association with HGS in the dominant hand divided by waist circumference (WC) and with HGS in the dominant hand divided by WHtR. In women, OA showed a strong association with body mass index. RA was strongly associated with HGS in both hands and HGS in the dominant hand divided by height. Finally, OR-arthritis was strongly related to HGS in both hands divided by WC and HGS in both hands divided by weight. Discussion The prevalence of OA was much greater than that of RA in both sexes. We found that the best index among anthropometric, absolute HGS, and relative HGS indices differed according to OA, RA, and OR-arthritis status and sex. The clinical implication of this study is that the association between RA and HGS was greater than that between OA and HGS in both sexes.